Understanding the Communication Strategy of Women's Rights Protection in the Digital Era through Website - Zinaida, Rahma Santhi; Havivi, Siti Lady (Universitas Semarang, 2019)
The National Commission on Violence Against Women in Indonesia through their website, release that there are three women who become victims of sexual violence every two hours. Kalyanamitra was chosen as the subject of the study because there are not many NGO s committed in protecting women's rights in Indonesia that have survived for more than 33 years. This study aims to explain how the communication strategy has been done in this organization through their official website. The important of doing this study is that can inspire other NGO s to optimize the use of online media. The theories used in this study are Media Rich Theory (MRT). This study use interpretative paradigm with the type of research is qualitative descriptive. Data were collected by using content analysis from website https://www.kalyanamitra.or.id/#. As the result, Kalyanamitra has done effective communication strategy by using techniques such as canalizing, informative, persuasive, and also educative.